(untitled) (Agricultural Engineering, 2019)
The purpose of the supply chain management is to ensure a competitive advantage as well as specific added value for the benefit of all supply chain links. Appropriate management practices generate many benefits, allow for savings in particular segments of the supply chain by means of cost reduction, which in turn directly leads to the competitiveness of enterprises belonging to a specific chain. The above-mentioned issues have become the subject of this thesis. Therefore, the British American Tobacco distribution network is strategically analyzed. A location and number of distribution centers will be i.a. taken into account. Reduction in the number of distribution centers will be suggested in order to reduce logistics costs in the supply chain, i.e. transport and storage. The studies were carried out based on the analysis of flows and route planning of the logistics operator for the transport of the company's products.